Ethnic goods and immigrant assimilation - Ilhom Abdulloev; Gil S. Epstein; Ira N. Gang (Institut für Ost- und Südosteuropaforschung (IOS), 2014)
Some immigrants try to keep their ethnicity hidden while others become ever deeply more mired in their home culture. We argue that among immigrants this struggle manifests itself in the ethnic goods they choose to consume. Different types of ethnic goods have vastly different effects on immigrant assimilation. We develop a simple theoretical model useful for capturing the consequences of this struggle, illustrating it with examples of Central Asian assimilation into the Muscovite economy.
urn:nbn:de:101:1-201404088434
Keywords: J15; 330; assimilation; migrants; culture; ethnic goods